FMR study of thin films of Co2Cr0.6Fe0.4Al and Co2MnSi Heusler alloys - Rameev, B. Z.; Yildiz, F.; Kazan, S.; Aktas, B.; Rata, D.; Buergler, D.; Gruenberg, P. (Maik Nauka/Interperiodica/Springer, 2006)
The method of ferromagnetic resonance (FMR) was used to study magnetic properties of thin films of half-metallic ferromagnetic Heusler alloys Co2Cr0.6Fe0.4Al and Co2MnSi depending on the film thickness and the presence or absence of a vanadium buffer layer. It is shown that the FMR method is a highly efficient technique for studying nanoscale magnetic properties of thin films, especially for the investigation of their magnetic inhomogeneities and anisotropy. Samples of Co2Cr0.6Fe0.4Al and Co2MnSi were prepared by magnetron-sputtering deposition on substrates of single-crystal silicon dioxide (SiO2) with an orientation (100). It has been shown that the magnetic properties of thin Co2Cr0.6Fe0.4Al films strongly depend on both the film thickness (25 or 100 nm) and the presence of an intermediate vanadium layer (50 nm). Well-resolved spin-wave modes were observed in the sample 100 nm thick without a vanadium buffer layer, which made it possible to determine the parameter of spin stiffness D for this ferromagnet. Two series of thin films of Co2MnSi have also been studied, which were prepared on a buffer layer of vanadium (42 nm thick): (1) with various thicknesses (4-100 nm) and a fixed annealing temperature (450 degrees C) and (2) with a fixed thickness (80 nm) and various annealing temperatures (425-550 degrees C). It has been shown that in the series of Co2MnSi films with a variable thickness (4-100 nm) the greatest value of magnetization is reached for a film with a thickness of 61 nm. The investigations of the other series of films, which were annealed at various temperatures, show that to achieve both a greater magnetization and a better structural homogeneity, annealing at temperatures T >= 450 degrees C is required. In addition, low-intensity spin-waves were observed in some samples with thicknesses of 100 and 61 nm, which made it possible to estimate the spin-stiffness parameter D for the Co2MnSi Heusler alloy as well.
Keywords: Magnetic Anisotropies